EFEKTIVITAS PENGGUNAAN GYMBALL TERHADAP INTENSITAS NYERI PERSALINAN KALA I FASE AKTIF DI PUSKESMAS GANTAR KABUPATEN INDRAMAYU TAHUN 2026 - Dasih Purnama Dewi; Mira Meliyanti; Dyah Triwidiyantari; Ida Suryani (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2026)
Labor pain is a physiological response resulting from uterine contractions and cervical dilatation during the childbirth process. Inadequate pain management may increase maternal anxiety and tension, impair the effectiveness of uterine contractions, and contribute to prolonged labor. At the Gantar Community Health Center (UPTD Puskesmas Gantar), Indramayu Regency, cases of prolonged labor are still encountered and are presumed to be associated with suboptimal labor pain management, leading to increased maternal anxiety, reduced uterine contractility, and, in some cases, the need for referral to higher-level healthcare facilities. One of the non-pharmacological interventions that may help reduce labor pain intensity is the use of a gym ball. This study aimed to evaluate the effectiveness of gym ball use in reducing labor pain intensity during the active phase of the first stage of labor at the Gantar Community Health Center, Indramayu Regency, in 2026. A quasi-experimental study employing a one-group pretest–posttest design was conducted. The study included 36 women in the active phase of the first stage of labor who were selected using purposive sampling. Labor pain intensity was assessed before and after the intervention using a standardized pain observation scale. Before the intervention, most participants experienced severe pain (61.1%), while the remaining 38.9% reported moderate pain. Statistical analysis using the Wilcoxon Signed Rank Test revealed a significant reduction in labor pain intensity following the gym ball intervention (p = 0.001; p < 0.05). These findings demonstrate that gym ball use is an effective non-pharmacological intervention for reducing labor pain during the active phase of the first stage of labor and has the potential to improve maternal comfort throughout the childbirth process.